Trends of National and Subnational Incidence of Childhood Cancer Groups in Iran: 1990–2016 - Shabani, Mahsima; Saeedi Moghaddam, Sahar; Ataeinia, Bahar; Rezaei, Nazila; Mohebi, Farnam; Mohajer, Bahram; Gohari, Kimiya; Sheidaei, Ali; Pishgar, Farhad; Yoosefi, Moein; Kompani, Farzad; Farzadfar, Farshad (Frontiers in Oncology, 2020)
Background: Childhood cancer is a double-edged sword, considering its high rate of response to treatment despite a high vulnerability to develop future malignancies in survivors. Thus, multidisciplinary preventive, curative, and supportive strategies must be incorporated in childhood cancer care that require understanding the distribution and trend of cancer in the target population. In this article, we aimed to report the national and subnational trends of childhood cancer incidence in Iran from 1990 to 2016, and mortality/incidence ratio (MIR), which, to our knowledge, have not been reported in previous literature. Method: Data on the incidence and mortality rates were collected from the National and Subnational Burden of Diseases project. We employed a two-stage spatiotemporal model to estimate cancer incidences by sex, age, province, and year based on the primary dataset of national death registration system. National and subnational age and gender-specific trends as well as MIR were calculated. Result: The age-standardized incidence rate had a steady increasing trend for cancers in both female [annual percent change (APC), 1.6%] and male (APC, 2.1%) patients. Not only there was an increasing trend in most provinces but also there was a 40% divergence in age-standardized incidence rate at subnational levels. Leukemia, lymphoma, neoplasms of the central nervous system (CNS), digestive tract, endocrine gland, and urinary tract were the leading causes of cancer comprising more than half of all cancers. There was a remarkable general decrease in MIR by 75% as a proxy of care quality. Conclusion: Regarding the increased trend of childhood cancer incidence, there is an essential need to address the etiologic factors and establish preventive plans for childhood cancers. Despite the favorable outcomes observed in cancer care, commensurate health resource allocation must be applied to diminish the subnational disparities.